Perceived positive and negative consequences after surviving cancer and their relation to quality of life. Issue 3 (6th February 2015) - Castellano‐Tejedor, Carmina; Eiroa‐Orosa, Francisco‐José; Pérez‐Campdepadrós, Marta; Capdevila, Lluís; Sánchez de Toledo, José; Blasco‐Blasco, Tomás
<x xml:space="preserve">Abstract</x> Surviving childhood cancer has multiple implications on both physical and psychological domains of the individual. However, its study and possible effects on health‐related quality of life (HRQoL) outcomes of adolescent survivors has been understudied. The objective of this study was twofold; to assess positive and negative cancer‐related consequences (psychosocial and physical) in a sample of adolescent cancer survivors and to explore their relationship with HRQoL outcomes. Forty‐one participants answered two questions about positive and negative consequences in the aftermath of cancer and filled in the KIDSCREEN‐52 self‐reported version. Data were analysed using mixed methods approach. Overall, 87.8% of the studied sample identified positive consequences and 63.4% negative consequences in survivorship. Four positive categories and five negative categories with regard to cancer‐related consequences were found. Changed perspectives in life narratives seem to be the positive consequence more related to HRQoL (physical well‐being, mood & emotions, autonomy, social support & peers), followed by useful life experience (physical well‐being, autonomy, social support & peers). Psychological impact was the most referred negative consequence with a significant detrimental effect on social support and peers HRQoL dimension. Even if the majority of survivors reported benefit finding in the aftermath of cancer, concomitant positive and negative consequences have been found. However, findings only reveal a significant relationship between positive narratives and HRQoL, and negative consequences do not seem to have a significant influence on overall HRQoL in survivorship.